2015
DOI: 10.1159/000368503
|View full text |Cite
|
Sign up to set email alerts
|

Diameter of Parathyroid Glands Measured by Computed Tomography as a Predictive Indicator for Response to Cinacalcet in Dialysis Patients with Secondary Hyperparathyroidism

Abstract: Background/Aims: Cinacalcet is one of the important treatments of secondary hyperparathyroidism (SHPT). We evaluated the role of computed tomography (CT) for parathyroid glands (PTGs) to determine the response to cinacalcet therapy in dialysis patients. Methods: In study 1, we compared the predictive cutoff values of the largest volume or diameter of PTGs on ultrasonography or CT for achievement of target intact parathyroid hormone (iPTH) level according to K/DOQI guideline after cinacalcet treatment in a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…La gammagrafía con Sestamibi marcado con Tecnecio 99m es la ideal, y su principal característica es la persistencia de la hipercaptación en imágenes tardías (a los 120 y 180 minutos) en el territorio que comparten la glándula tiroides y paratiroides (10). Una de las características importantes de las variedades de hiperplasia multinodular o uninodular de las glándulas paratiroides y que impacta en la decisión de sospecharlas, es la baja respuesta que presentan al tratamiento con vitamina D, análogos de la vitamina D, y calcimimeticos, lo que se explica por su carácter autónomo y reducción significativa que poseen en el número de receptores para la vitamina D activa y calcio, lo que ha sido demostrado en diversos estudios (11)(12)(13)(14)(15)(16). Situación semejante ocurre cuando el número de glándulas detectadas por imágenes es mayor de uno, en condiciones inclusive cuando su volumen es menor de 1000 mm 3 (1,0 cm 3 ) (17).…”
Section: Launclassified
“…La gammagrafía con Sestamibi marcado con Tecnecio 99m es la ideal, y su principal característica es la persistencia de la hipercaptación en imágenes tardías (a los 120 y 180 minutos) en el territorio que comparten la glándula tiroides y paratiroides (10). Una de las características importantes de las variedades de hiperplasia multinodular o uninodular de las glándulas paratiroides y que impacta en la decisión de sospecharlas, es la baja respuesta que presentan al tratamiento con vitamina D, análogos de la vitamina D, y calcimimeticos, lo que se explica por su carácter autónomo y reducción significativa que poseen en el número de receptores para la vitamina D activa y calcio, lo que ha sido demostrado en diversos estudios (11)(12)(13)(14)(15)(16). Situación semejante ocurre cuando el número de glándulas detectadas por imágenes es mayor de uno, en condiciones inclusive cuando su volumen es menor de 1000 mm 3 (1,0 cm 3 ) (17).…”
Section: Launclassified
“…The authors reported a statistically not‐significant post‐treatment decrease of PTG volume. Finally, Hong et al compared the predictive cutoff values of the largest volume or diameter of PTG measured by ultrasonography or computed tomography for achievement of K/DOQI guideline target of PTH level after cinacalcet. In univariate and multivariate logistic analysis, baseline PTH and the existence of PTG ≥ 11.2 mm on CT significantly influenced the response to cinacalcet treatment.…”
Section: Current Problem Of Management Of Shpt: the State Of The Artmentioning
confidence: 99%
“…The number of PTx decreased dramatically ( 5 , 9 ). Although calcimimetics are usually administered to treat SHPT, PTx is required in patients who do not respond to drug treatment and those who cannot tolerate calcimimetics because of drug allergies and adverse effects ( 9 13 ). Total PTx, transcervical thymectomy, and forearm autograft are frequently performed ( 1 , 14 ).…”
Section: Introductionmentioning
confidence: 99%